Movement pattern recognition ability of Malaysian rhythmic gymnastics judges - Kok, Lian Yee; Teh, Lah Hoong (Penerbit Universiti Malaysia Pahang, 2013)
This study examined the significance of movement pattern recognition ability in the judging performance of 30 rhythmic gymnastics judges who were classified correspondingly as expert, non-expert and novice. Results indicated that the expert and non-expert participants were superior to the novice participants in their movement pattern recognition ability and their judging performance but there were no differences between the expert and non-expert participants. When the participants were regrouped according to their movement pattern recognition ability; low, average and high, the results showed that there were very significant differences in the judging performances of the three groups classified according to their movement pattern recognition ability. This suggests that movement pattern recognition ability influences the judging performance of a rhythmic gymnastics judge.